Antibody-mediated protection against Ebola virus. (November 2018) - Saphire, Erica; Schendel, Sharon; Gunn, Bronwyn; Milligan, Jacob; Alter, Galit
Abstract Recent Ebola virus disease epidemics have highlighted the need for effective vaccines and therapeutics to prevent future outbreaks. Antibodies are clearly critical for control of this deadly disease; however, the specific mechanisms of action of protective antibodies have yet to be defined. In this Perspective we discuss the antibody features that correlate with in vivo protection during infection with Ebola virus, based on the results of a systematic and comprehensive study of antibodies directed against this virus. Although neutralization activity mediated by the Fab domains of the antibody is strongly correlated with protection, recruitment of immune effector functions by the Fc domain has also emerged as a complementary, and sometimes alternative, route to protection. For a subset of antibodies, Fc-mediated clearance and killing of infected cells seems to be the main driver of protection after exposure and mirrors observations in vaccination studies. Continued analysis of antibodies that achieve protection partially or wholly through Fc-mediated functions, the precise functions required, the intersection with specificity and the importance of these functions in different animal models is needed to identify and begin to capitalize on Fc-mediated protection in vaccines and therapeutics alike. Saphire and colleagues provide new insight into protective antibody-mediated responses to Ebola virus and how these responses could be harnessed for therapeutic intervention and vaccine strategies.